Comprehensive physiotherapy before and after abdominoplasty – a case study - Radzimińska, Agnieszka (Journal of Education, Health and Sport, 2025)
Introduction Abdominoplasty, also known as abdominal wall plastic surgery, is one of the most commonly performed plastic surgery procedures. It involves removing excess skin and fat tissue from the abdominal area (which could not be removed through diet and exercise), as well as stitching the rectus abdominis muscles and restoring the continuity of the linea alba in the event of its separation. During the operation, the surgeon also strengthens the structure of the fascia. The operation is performed under general anesthesia, which increases the risk of postoperative complications. The aim of comprehensive physiotherapy is to prepare the patient for the procedure and to speed up recovery after the surgery. The main aim of pre-operative rehabilitation is to teach how to perform breathing and anticoagulant exercises and to educate about verticalization after the procedure. The physiotherapist also explains methods for safely changing position in bed, the rules for getting up and getting into bed. He recommends the selection of special orthopedic wedge pillows on which the patient will lie after the procedure for 2-3 weeks. Numerous scientific reports indicate the beneficial effects of pre- and post-operative rehabilitation. Objectives The aim of the article was to present comprehensive physiotherapy before and after abdominoplasty performed on a 42-year-old patient due to excess skin folds in the abdominal area and separation of the rectus abdominis muscles. Preparing the patient for surgical treatment requires cooperation between the physiotherapist and the surgeon performing the procedure. The comprehensive rehabilitation program was developed based on our own experience in working with patients after abdominoplasty and analyzing specialist bibliography. Conclusions Pre-operative rehabilitation aims to teach the patient breathing and anticoagulant exercises. 2. Before surgery, the physiotherapist educates the patient on verticalization after the procedure, discusses methods of safe change of position in bed, rules of getting up. Recommends the selection of special orthopedic wedge pillows on which the patient will lie after the procedure. Moderate and controlled physical activity is a recommended preventive intervention to reduce postoperative complications. Pelvic floor muscle training and upper rib and lower rib breathing exercises support the healing process of the tissues in the abdominal cavity. Lymphatic drainage is an effective method of reducing swelling of the abdominal wall after the procedure. The scar after abdominoplasty requires manual therapy dedicated to the prevention of adhesions. Physiotherapists should create an individual comprehensive physiotherapy program for patients who are first qualified for surgical treatment and then undergo abdominoplasty. In order to better prepare for the procedure, the patient should follow the nutritional recommendations.